Evaluation of protease resistance and toxicity of amyloid-like food fibrils from whey, soy, kidney bean, and egg white. (1st February 2016) - Lassé, Moritz; Ulluwishewa, Dulantha; Healy, Jackie; Thompson, Dion; Miller, Antonia; Roy, Nicole; Chitcholtan, Kenny; Gerrard, Juliet A.
Highlights: Food fibrils were non-toxic to Caco-2 and Hec-1a cell lines in vitro . Native protein and fibrillar protein had similar effects on cell viability. Fibrils showed varied resistance to digestion by Proteinase K, pepsin, or pancreatin. Abstract: The structural properties of amyloid fibrils combined with their highly functional surface chemistry make them an attractive new food ingredient, for example as highly effective gelling agents. However, the toxic role of amyloid fibrils in disease may cause some concern about their food safety because it has not been established unequivocally if consumption of food fibrils poses a health risk to consumers. Here we present a study of amyloid-like fibrils from whey, kidney bean, soy bean, and egg white to partially address this concern. Fibrils showed varied resistance to proteolytic digestion in vitro by either Proteinase K, pepsin or pancreatin. The toxicity of mature fibrils was measured in vitro and compared to native protein, early-stage-fibrillar protein, and sonicated fibrils in two immortalised human cancer cell lines, Caco-2 and Hec-1a. There was no reduction in the viability of either Caco-2 or Hec-1a cells after treatment with a fibril concentration of up to 0.25 mg/mL.